Participatory or deliberative democracy? Exploring the mediation effects of perceived online deliberation and online interactive activities on social outcomes. Issue 2 (May 2015) - You, Kyung Han; Lee, Jeong Kyu; Kang, Hyunjin; Go, Eun
Highlights Political news had strong effects on social outcomes both directly and indirectly. Entertainment news indirectly influenced political participation via news blogging. Perception of deliberation moderated an effect of political news on participation. News blogging mediated the relation between two types of news and participation.